Border Crossing Knowledge Systems: A PNG Teacher’s Autoethnography - Reta, Medi (The Australian Journal of Indigenous Education, 2010)
Abstract Narratives have always been integral to Indigenous knowledge transfer. In this autoethnography the author shares her border crossings between her Indigenous knowledge systems and the often dominant Western knowledge system. Pertinent to these experiences are the stark contrasts that exist between the two knowledge systems and their educational goals. This paper opens up space for conversation amongst those educators who are keen to learn and enhance their teaching and learning experiences in schools, particularly of those students whose cultural background differs from their own.